ANALISIS PENGGUNAAN LIMBAH B3 SPENT BLEACHING EARTH SEBAGAI BAHAN BAKAR ALTERNATIF DI PT. SEMEN BATURAJA (PERSERO) TBK: Limbah B3, Spent Bleaching Earth (SBE), Bahan Bakar Alternatif, Rotary Kiln, Clinker - Robiansyah; Mustain; Martha Aznury; Safaruddin (KINETIKA, 2022)
Hazardous waste of Spent Bleaching Earth (SBE) which is processed by PT. Semen Baturaja (Persero) Tbk is used asan alternative fuel to replace coal, whose price continues to rise, because SBE still contains oil in it. However, the useof hazardous waste of SBE can affect the specific heat consumption needed in the operation of the rotary kiln machineand the ash content in it can affect the quality of the clinker produced. With the percentage of SBE alternative fuelmixture to coal fuel of 0%, 1,12%, 2,07%, 3,13%, 4,09%, 4,93%, 6,13% and 6,88%, the analysis carried out on ofspecific heat consumption, fuel cost efficiency, rotary kiln machine operation and its effect on the quality of the clinkerproduct produced. From the results of this case study, with an increase in the percentage of the SBE mixture, the ashvalue of the mixed fuel trend to increase but is not significant, while the calorific value of this fuel mixture trend todecrease. The conclusion that can be drawn from the use of hazardous waste of SBE as an alternative fuel with amixture percentage of 0% to 6.88% is that as the fuel mixture ratio increases, specific heat consumption decreases,fuel cost efficiency increases, fuel requirements become lower, compared to not using hazardous waste of SBEalternative fuel and has no significant effect on the quality of the clinker product produced.Key words: Hazardous waste, Spent Bleaching Earth (SBE), Alternative fuel, Rotary kiln, Clinker